FNA Cytology in pediatric small cell glioblastoma - Kalogerak, Alexandrai; Tamiolakis, Dimitrios; Zoi, Iris; Karvela-Kalogeraki, Iliana; Karvelas-Kalogerakis, Mihailos; Segredakis, John; Datseri, Galateia (Acta Biomedica Atenei Parmensis, 2018)
Small cell glioblastoma is a high anaplastic variant of GBM characterized by a monomorphic proliferation of small or medium cells with oval nuclei and scanty cytoplasm. Case study: The cytologic findings of a small cell glioblastoma in 11-year-old male and histologic features of the tumor using immunocytohistochemistry are reported. Conclusion: The accurate preoperative diagnosis of a small cell glioblastoma is crucial to developing a curative surgical plan. Cytology- confirmed by histology- provides a convenient, safe and effective approach to solving a challenging differential diagnosis.